Microbiota in Obesity - Mohd Adzim Khalili, Rohin; Uday Younis, Hussein; Atif, Amin Baig (2014)
The obesity epidemic is globally considered as one of the topmost health concern whose multifactorial etiology involves sedentary life style, poor dietary habit, individual’s genetic peculiarity, environmental factors, adipose tissue inflammation and many more. More recently, researchers are intensively focusing on the role of gut microbiome in the manifestation and pathogenesis of obesity and associated complications. Microbiomes modulation of inflammatory responses associated to physiology of obesity implicated the involvement of the Toll-like receptors (TLRs), Short-chain fatty acids (SCFAs) response, gut fermentation mechanisms, as well as passive immune defense exerted by refining of mucous barriers in response to bacterial presence. We reviewhere the role of gut microbiota in the pathogenesis and management of obesity as it relates to metabolic inflammation. Accurate alteration of the gut microbiome appears to be a potential therapeutic intervention that may impede white adipose tissue inflammation and in the long run prevent obesity.